Pendekatan Transfer Learning untuk Klasifikasi Penyakit Mata Menggunakan Citra dengan CNN InceptionV3 - Gunawan, Rahmad; Fathurrahman, Raihan; Widyaningrum, Amelia Ismania Sita; Issandra, Febri; Abdurachman, Muhammad Andhika; Putra, Yogi Ernanda; Naufal (Universitas Muhammadiyah Riau, 2025)
Eye diseases are a leading cause of vision impairment and blindness worldwide. Therefore, detection of eye diseases is crucial in the prevention of blindness. This study develops an eye disease classification model based on Convolutional Neural Network (CNN) using Transfer Learning with InceptionV3. The dataset consists of 1559 images, divided into 1249 training images and 310 validation images, covering 8 eye disease classes. The model was trained using 40 epochs with the Adam optimizer. Evaluation results show a validation accuracy of 81.29%. While the model performed well, some classes, such as hordeolum, showed lower accuracy, indicating areas that need further improvement. This study confirms that Transfer Learning with InceptionV3 is an effective approach for eye disease classification.